Pelatihan Peningkatan Kemampuan Technological Pedagogic Content Knowledge Guru Sekolah Dasar Pada Pembelajaran Matematika - Syafri Ahmad; Zelhendri Zen; Masniladevi Masniladevi; Ary Kiswanto Kenedi; Sherlyane Hendri (Jurnal Pemberdayaan Masyarakat, 2022)
This training was motivated by the low TPACK ability of elementary school teachers in the mathematics learning process. The purpose of this activity is to improve the TPACK ability of elementary school teachers in learning mathematics. The implementation method is by carrying out training activities in Cluster II, Pauh District, Padang City, involving 30 elementary school teachers. The results of the activity stated that there was an increase in the TPACK ability of elementary school teachers in learning mathematics. The implications of this activity can be used as a reference in developing the TPACK abilities of elementary school teachers.